Numerical Simulation of Vehicles Queue Induced by Traffic Light Signals Based on Macroscopic Approach - Tarwidi, Dede; Budi Setiawan, Erwin; Febrian Umbara, Rian (International Journal of Engineering and Technology, 2019)
A disproportionate adjustment of traffic light signals on crowded intersections has become one of the cause of a traffic congestion in big cities. To control traffic congestion in a signalized intersection, it is required a prediction of vehicles queue length induced by traffic light signals every time. In this paper, numerical simulation of vehicles queue in three roads which is connected by an intersection is presented. The Lighthillâ€“Whithamâ€“Richards (LWR) model which is considered as macroscopic model is used to describe traffic density at the single road. Godunov method is adopted to obtain numerical solution of LWR model. The numerical results of vehicles queue length are then compared by observational data at a signalized intersection in Bandung city. The LWR model can predict the vehicles queue length with the accuracy is approximately 85.33%.Â